2008
DOI: 10.2478/s11536-007-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in patients after cardiac valve surgery

Abstract: AbstractThe aim of study was to analyze heart rate variability (HRV) after different cardiac valve surgery procedures and the prognostic values of these findings. This study included 101 consecutive patients who underwent surgical implantation for an artificial valve. The mean age of the patients was 62 ± 10 years. An aortic valve was implanted in 65 patients. A mitral valve was implanted in 36 patients. HRV was analyzed from 24 hours Holter electrocardiographic (ECG) records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
3
12
0
1
Order By: Relevance
“…Moreover, many studies have demonstrated that coronary artery bypass grafting (CABG) also leads to significant HRV reduction, which is even more pronounced than after myocardial infarction [10][11][12][13]. In addition, HRV reduction after cardiac surgery is not exclusively related to PCI or CABG, as it is also recorded in patients undergoing valve surgery [14]. Unlike myocardial infarction where the main reason of the HRV reduction is ischaemia and myocyte necrosis, the probable reasons for considerable HRV reduction immediately after PCI or CABG include a combined effect of surgical manipulation during operative procedure on the heart and adjacent anatomical structures, prolonged anaesthesia [29,30] and cardioplegia [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many studies have demonstrated that coronary artery bypass grafting (CABG) also leads to significant HRV reduction, which is even more pronounced than after myocardial infarction [10][11][12][13]. In addition, HRV reduction after cardiac surgery is not exclusively related to PCI or CABG, as it is also recorded in patients undergoing valve surgery [14]. Unlike myocardial infarction where the main reason of the HRV reduction is ischaemia and myocyte necrosis, the probable reasons for considerable HRV reduction immediately after PCI or CABG include a combined effect of surgical manipulation during operative procedure on the heart and adjacent anatomical structures, prolonged anaesthesia [29,30] and cardioplegia [10].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have invariably demonstrated that coronary artery bypass grafting (CABG) also leads to significant HRV reduction [10][11][12][13]. In addition, HRV reduction after cardiac surgery is not exclusively related to PCI or CABG, as it is also recorded in patients undergoing valve surgery [14]. However, opposite conclusions still exist to show the HRV reduction after PCI is not significant [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been already described that the derangement of HRV after cardiac valve surgery may persist up to various months after intervention [11]. After both coronary artery by-pass surgery and valvular surgery, the greatest impairment of cardiac autonomic function and the maximal decrease of HRV parameters is reported to occur at about the sixth postoperative day, persisting rather low at 15 days after intervention [9,15], approximately the time our SAVR patients had been studied with a 24-h Holter recording.…”
Section: Discussionmentioning
confidence: 99%
“…A very limited number of papers reported that HRV decreases also in patients undergoing valvular heart surgery, and that cardiovascular autonomic dysfunction seems to be more pronounced and persisting for longer period after mitral valve surgery than aortic valve surgery [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree of impairment can be assumed to vary with the type of intervention, i.e., which valve is concerned, and chosen operational procedure. In this regard, Lakusic et al [9] showed that the impairment in autonomic function 3.8 months after surgery was much more pronounced for mitral valve implantation compared to aortic valve implantation.…”
Section: Introductionmentioning
confidence: 99%